THE «SPECIAL» RELATIONSHIP BETWEEN GERMANY AND CHINA IN THE CONTEXT OF GERMANY’S CHINA POLICY - A. V. Tsvyk (Vestnik MGIMO-Universiteta)
The Federal Republic of Germany and the People's Republic of China are both economic powers in Asia and Europe with a shared international responsibility in many international fields. Germany is China's number-one trade partner in the EU and China is the top foreign investment destination for German companies. This article highlights the relationship between Germany and China since the beginning of Gerhard Schroeder's «Wandel dutch Handel» policy in 1998. Germany's policy toward China was based on the idea that economic exchange and increase in trade between both countries would lead to political and societal change in China. In the author's point of view Germany's China policy shifted significantly to one which focused more heavily on human rights at the beginning of the first term under Chancellor Angela Merkel in 2005. The author argues that Germany's China policy at present time is motivated first of all by economic interests and the needs of its exporters. In recent years, there have been efforts to extend cooperation to other fields like security and world order. The author comes to the conclusion that both Germany and China increasingly consider a strategic partnership within mutual interest.